Singing 'with culture': popular musicians and affective labour in state-socialist Albania. Issue 3 (2nd September 2017) - Tochka, Nicholas
ABSTRACT: This article examines how composers, bureaucrats and musicians themselves disciplined the singer's body in state-socialist Albania. Drawing together film analysis and interviews with socialist-era musicians, I analyse the constraints imposed on performing bodies in order to explore the political consequences of singers' affective labour during the 1970s and 1980s. My analysis reveals how the most popular stars crafted performing personae, as 'cultured' citizens, and conceptualised the social significance of their affective labour, as part of a broader political project aiming to uplift listeners. In negotiating these dual aims, singers simultaneously created musically and personally meaningful lives while participating in state-socialist projects to remake society. In describing the political consequences of affective labour in this particular non-capitalist context, the article contributes to recent studies of eastern bloc cultural economies, while also problematising the status of 'affective labour' as an analytical valence in ethnomusicology.